Analisis Implementasi Reverse Logistics untuk Meningkatkan Efisiensi Biaya dalam Pengelolaan Limbah Medis di Klinik Kesehatan - Foci, Nia Arfina; Nur, Rahmi M; Salsabila, Syafira; Yasin, Muhamad; Munanda, M Arif (Greeners: Journal of Green Engineering for Sustainability, 2025)
Medical waste management is a major challenge in the health system, especially in ensuring cost efficiency while minimizing environmental impacts. This study aims to analyze the relationship between the application of reverse logistics and the cost efficiency of medical waste management in health clinics. The methodology used is a quantitative approach with a sample of 36 respondents involved in medical waste management. Data was collected using a questionnaire and analyzed using the Chi-Square test to evaluate the relationship between variables. The research results show a significant relationship between the implementation of reverse logistics and cost efficiency, where better implementation can substantially reduce operational expenditure. The conclusions of this research indicate that medical waste management through reverse logistics effectively increases cost efficiency, and supports environmental sustainability. The practical implications of these findings can be a reference for health clinic managers in designing more efficient waste management strategies.